Biocompatible glyconanomaterials based on HPMA-copolymer for specific targeting of galectin-3 - Bojarová, P; Tavares, M R; Laaf, D; Bumba, L; Petrásková, L; Konefał, R; Bláhová, M; Pelantová, H; Elling, L; Etrych, T; Chytil, P; Křen, V (Journal of nanobiotechnology, 2018)
BACKGROUND: Galectin-3 (Gal-3) is a promising target in cancer therapy with a high therapeutic potential due to its abundant localization within the tumor tissue and its involvement in tumor development and proliferation. Potential clinical application of Gal-3-targeted inhibitors is often complicated by their insufficient selectivity or low biocompatibility. Nanomaterials based on N-(2-hydroxypropyl)methacrylamide (HPMA) nanocarrier are attractive for in vivo application due to their good water solubility and lack of toxicity and immunogenicity. Their conjugation with tailored carbohydrate ligands can yield specific glyconanomaterials applicable for targeting biomedicinally relevant lectins like Gal-3. RESULTS: In the present study we describe the synthesis and the structure-affinity relationship study of novel Gal-3-targeted glyconanomaterials, based on hydrophilic HPMA nanocarriers. HPMA nanocarriers decorated with varying amounts of Gal-3 specific epitope GalNAcβ1,4GlcNAc (LacdiNAc) were analyzed in a competitive ELISA-type assay and their binding kinetics was described by surface plasmon resonance. We showed the impact of various linker types and epitope distribution on the binding affinity to Gal-3. The synthesis of specific functionalized LacdiNAc epitopes was accomplished under the catalysis by mutant β-N-acetylhexosaminidases. The glycans were conjugated to statistic HPMA copolymer precursors through diverse linkers in a defined pattern and density using Cu(I)-catalyzed azide-alkyne cycloaddition. The resulting water-soluble and structurally flexible synthetic glyconanomaterials exhibited affinity to Gal-3 in low μM range. CONCLUSIONS: The results of this study reveal the relation between the linker structure, glycan distribution and the affinity of the glycopolymer nanomaterial to Gal-3. They pave the way to specific biomedicinal glyconanomaterials that target Gal-3 as a therapeutic goal in cancerogenesis and other disorders.
Keywords: galektin 3; Galectin-3; Nanostructures; Blood Proteins; Carbohydrate; Acrylamides; glykokonjugáty; nanostruktury; Galectin 3; Glycoconjugates; Drug Carriers; Surface plasmon resonance; Galectins; ELISA; Drug Delivery Systems; krevní proteiny; lidé; HPMA copolymer; Humans; Glyconanomaterial; akrylamidy; nosiče léků; galektiny; lékové transportní systémy